Surface properties and photocatalytic activity of nanostructural films - Yatskiv, V.I.; Petrik, I.S.; Smirnova, N.P.; Granchak, V.M.; Eremenko, A.M. (Functional Materials, 2004)
Glass-supported TiO₂ nanostructural films of various porosity have been prepared. The structure and sorption characteristics of the obtained coatings have been investigated by x-ray phase analysis, adsorption methods and transmission electron microscopy. The photocatalytic activity of prepared materials in the gas-phase oxidation of ethanol and acetone has been examined. Besides the specific photocatalytic activity of ТІО₂ (anatase), photocatalyst sorption capacity defined by ТІО₂ coating porosity was also found to exert a decisive influence upon efficient photooxidation in gaseous phase. Получены наноструктурные пленки ТІО₂ различной степени пористости, нанесенные на стеклянные подложки. Методами рентгенофазового анализа, адсорбции и трансмиссионной электронной микроскопии изучены структурно-сорбционные характеристики полученных пленок, исследована их фотокаталитическая активность в реакциях окисления ацетона и этанола в газовой фазе. Показано, что определяющее значение для эффективного газофазного фотоокисления, кроме собственной фотокаталитической активности ТІО₂ (анатаза), имеет также сорбционная способность фотокатализаторов, которая определяется пористостью ТЮ₂-покрытий. Одержано наноструктурні плівки ТІО₂ різного ступеня пористості, нанесеш на скляні підкладки. Методами рентгенофазового аналізу, адсорбції та трансмісійної електронної мікроскопії досліджено структурно-сорбційні характеристики одержаних плівок, вивчено їх фотокаталітичну активність в реакціях окислення ацетону та етанолу у газовій фазі. Показано, що визначальний вплив для ефективного газофазного фотоокислення, окрім власної фотокаталітичної активності ТІО₂ (анатазу), має також сорбційна здатність фотокаталізаторів, яка визначається пористістю ТІО₂-покриттів.